Kecemasan Tokoh Haru Kato dalam Anime Fugou Keiji: Balance: Unlimited: Penelitian - Nadia Hana Zhafira; Arza Aibonotika; Hana Nimashita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to identify and describe the forms of anxiety experienced by the character Haru Kato in the anime Fugou Keiji: Balance: Unlimited. The character Haru Kato has a brave, honest, and morally upright personality as a detective, but when investigating cases, he tends to feel anxious and worried. The uniqueness of this character is his highly emotional personality, while his profession as a detective requires him to better control his emotions.The research method used is qualitative descriptive with an observation technique, specifically analyzing scenes and dialogues in the anime. This research employs a psychoanalytic approach based on Sigmund Freud's theory, focusing particularly on anxiety. Haru Kato's anxiety is demonstrated through events and dialogues between Haru Kato and other characters. In this anime, feelings of worry, doubt, and anger are forms of Haru Kato's anxiety. These arise from conflicts around Haru Kato that are inconsistent with the moral values he holds. The results of this study indicate that the forms of anxiety experienced by Haru Kato are moral anxiety, realistic anxiety, and neurotic anxiety.